2020
DOI: 10.14744/eej.2020.37450
|View full text |Cite
|
Sign up to set email alerts
|

Heat Induced Alterations of the Endodontically Treated Teeth for the Forensic Identifications: An in Vitro Study

Abstract: Objective: The study aimed to highlight the relationship between forensic science and endodontics by illustrating CBCT records can be used as legal evidence for forensic analysis and evaluate the effect of elevated temperature on the endodontically treated teeth. Methods: The present study was conducted on 40 extracted permanent mandibular premolars, which were divided into two groups based on predetermined incineration temperature: Group I - 400°C & Group II - 800°C su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
0
0
1
Order By: Relevance
“…1000 °C exposure caused greyish white color of the roots, while they were keeping relatively integrated conditions with deep fractured lines [13]. Results of the in-vitro study has revealed that even under the 800 °C exposure root portion of tooth in contrast to crown portion remained enough intact for being used for the analysis even though vertical crack present along root were present, while also guttapercha could be identified within root canal as a result of previous endodontic treatment, which was also proved by CBCT scan analysis [11]. Other study also approve root crack formation when tooth was exposed to 800 °C temperature [14].…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…1000 °C exposure caused greyish white color of the roots, while they were keeping relatively integrated conditions with deep fractured lines [13]. Results of the in-vitro study has revealed that even under the 800 °C exposure root portion of tooth in contrast to crown portion remained enough intact for being used for the analysis even though vertical crack present along root were present, while also guttapercha could be identified within root canal as a result of previous endodontic treatment, which was also proved by CBCT scan analysis [11]. Other study also approve root crack formation when tooth was exposed to 800 °C temperature [14].…”
Section: Resultsmentioning
confidence: 76%
“…Previous review on the topic dedicated to the endodontic images as a potential forensic identification evidences has been already provided [2], but not all aspects of endodontic-related signs and their role within forensic odontology practice were covered in available publication. Tooth root retain its primary configuration and relative integrity even under the high temperature exposure, which make it possible to use such for the identification of burnt victims [1,10,11]. Cross-sectional study demonstrated that obturated single root radiographic images characterized with high level of specificity and evidence significance for decision making within forensic dentistry practice and dental identification process [9].…”
Section: Introductionmentioning
confidence: 99%
“…De hecho, algunos investigadores buscaron relacionar la odontología forense con la endodoncia, utilizando las imágenes producidas por la TCHC para evaluar el efecto de la temperatura en dientes tratados endodónticamente, como la hacen Patel et al . 37 , quienes tomaron 40 premolares mandibulares tratados endodónticamente y los sometieron a temperaturas de 400 y 800 °C por 15 minutos (grupos de 20 dientes a cada temperatura), y realizaron tomografías a cada diente posteriormente. Se realizaron análisis odontológicos forenses macro y microscópicos a cada diente pre y post mortem , y se concluyó que todas las unidades dentarias sufren cambios macroscópicos y microscópicos a altas temperaturas, y si son analizados mediante la TCHC el estrés térmico produce cambios notables en la obturación tridimensional de los dientes tratados, por lo que resulta de utilidad en las ciencias forenses para la identificación de un cadáver calcinado.…”
Section: Discussionunclassified
“…Urooge and Patil [24] evaluated the CBCT of the maxillary sinus and reported that the efficiency of maxillary sinuses in sex identification was 74% in females and 68% in males. Moreover, a study conducted by Patel et al [25] focused on assessing the potential of CBCT records as legal evidence for forensic analysis. The researchers specifically examined CBCT images of teeth before and after incineration to determine if the features necessary for identification were preserved.…”
Section: Reviewmentioning
confidence: 99%